User Perception based Evaluation of Bus Terminal Facilities in Dhaka City, Bangladesh - Reza, Farhadur; Amin, Yeasir Mohammad; Tasnuma (International Journal of Social Sciences and Management, 2025)
In urban transportation network, bus terminals are critical nodes that serve the citizens largely. The Mohakhali Bus Terminal in Dhaka, Bangladesh, a pivotal inter-district transport hub facilitating approximately 800 daily trips, currently experiences significant constraints due to infrastructural and managerial inadequacies. Grounded in user perception, this research employs an evaluation framework to thoroughly analyze the terminal's facilities and operational conditions, identifying core deficiencies and formulating evidence driven, sustainable solutions. Adopting an exploratory and descriptive methodology, the research integrates passenger interviews (n=110), stakeholder interviews (n=10), and secondary data analysis. The key findings reveal systemic shortcomings in passenger amenities, including inadequate sanitation facilities, suboptimal lighting, limited universal accessibility, and the absence of digital information systems. Further, functional inadequacies in bus bay design, pedestrian infrastructure, and on site security further hinder the overall user experience. Additionally, institutional weaknesses, including insufficient staff facilities and lack of structured maintenance protocols, exacerbate these functional challenges. To address these challenges, the study recommends comprehensive improvements including infrastructural upgradation, integration of digital system, and administrative coordination by Dhaka North City Corporation. Int. J. Soc. Sc. Manage. Vol. 12, Issue-3: 141-149.